Salinity and nutrient effects on plant growth, physiology and fruit quality of rockmelon (Cucumis melo L.) cultivated under soilless system - Al-Mahrouqi, Yaqoob Ali Nasser (2018)
Salinity possesses challenges for agriculturalist to obtain optimum crop productions, yet could be employed as one of management strategies to modulate better quality of produce. In most cases, salinity potentially restricts nutrients balance, growth and production in many crops due to poor major nutrients availability and macronutrients deficiencies. Therefore, the overall objective of this study was to investigate the interactive effects of salinity and macronutrients on plant growth, physiology and fruit quality of melon (Cucumis melo L.) grown under soilless media system.